Answer:
C
Step-by-step explanation:
(f - g)(x)
= f(x) - g(x)
= 5x² - 3 - ( x² - 4x - 8) ← distribute parenthesis by - 1
= 5x² - 3 - x² + 4x + 8 ← collect like terms
= (5x² - x² ) + 4x + (- 3 + 8)
= 4x² + 4x + 5
Answer:
The answer is C. (f-g)(x) simplifies to 4x²+4x+5
b. 24
c. 29
d. 30
Answer:33 %
Step-by-step explanation:
Given
60 % of company A's employees are considered top performer
55 % of company A's employee are in a rigorous training program.
Now Company A's employees in the rigorous training program considered top performer are
That is 33 % of employee is in rigorous training and top performers.
Answer:
324
Step-by-step explanation:
Answer:
(2^6)(x^9^6) / 1814
Simplifies to:
1 / 5856458868470016^x531441
=
1 / 5856458868470016^x531441
Step-by-step explanation:
Which statements are true about adding the rational expressions? Check all that apply
The least common denominator is 20p
.
The first fraction rewritten with the LCD is 20p^2+30 / 20p^2
The second fraction rewritten with the LCD is 4p - 4 / 20p
The sum is 24p^2-,4p+30 / 20p^2 = 12p-2p+15 / 10p^2
The sum is a rational expression.
Answer:
37°
Step-by-step explanation:
angle B = angle D (alternate angle)
2X = 74°
X = 37°
Answer:
29
Step-by-step explanation:
right in acellus